Innovation in Natural Fiber Agroindustry Development: Business Model Canvas Approach and Ten Types of Innovation at Seratnusa - Dwi Purnomo; Healthy Nirmalasari; Gita Noerwardhani; Ferdyansyah Wicaksono; Rivaldi Rizki Ramdani (Agroindustrial Journal, 2026)
This study investigates how the integration of the Business Model Canvas (BMC) and the Ten Types of Innovation Framework facilitates the development of a sustainable business model for natural fibre-based agribusiness. Increasing consumer awareness of sustainability and the need for inclusive innovation models have created opportunities for small enterprises to strengthen competitiveness through collaboration and co-creation. Using the case of Seratnusa—a company producing eco-friendly products from agricultural fibers such as banana pseudostems—this research examines how customer co-creation and partnership-led innovation contribute to value creation and business sustainability. A qualitative case study approach was employed, combining semi-structured interviews with key stakeholders, direct observations, and document analysis. Findings reveal that integrating BMC with the Ten Types of Innovation enables Seratnusa to build strategic partnerships with e-commerce platforms, creative communities, and local artisans while engaging customers in product development and brand advocacy. These innovations enhance customer engagement, foster shared value, and expand access to global markets. The study underscores the importance of collaborative innovation in driving sustainable agribusiness transformation. Future research could examine how co-creation and partnership-led approaches influence long-term business resilience and sustainability across different agricultural value chains.